Microfocus X‐ray scattering and micro‐Raman spectroscopy: Transcrystallinity in isotactic polypropylene. Issue 8 (2nd June 2014) - Santoro, Gonzalo; Yu, Shun; Krywka, Christina; Roth, Stephan V.; Ellis, Gary
<x xml:space="preserve">Abstract</x> Microfocus X‐ray scattering and micro Raman spectroscopy have been applied to study the β‐transcrystalline morphology in isotactic polypropylene. The transformation from the α‐ to the β‐form through the so‐called bifurcation of growth mechanism has been investigated with high spatial resolution. We found that the mixed α–β region does not present spatial correlation along the shearing direction, implying that there is no cooperative crystallization from the different β‐nucleation centres. In addition, a strong change in the lamellar orientation of the α‐form thin layer that induces the growth of the β‐crystallites has been observed for the first time. Finally, changes in the relative intensities of some selected Raman bands allowed the observation of the α–β transformation process at the molecular level. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> (© 2014 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)